Foreign Exchange Rate Dynamics and Stock Market Performance in Nepal: A Vector Autoregressive Approach - Thapa, Krishna Bahadur; Lamichhane, Basu Dev (NPRC Journal of Multidisciplinary Research, 2025)
This study explores the dynamic relationship between foreign exchange rate (EXR) and stock market performance in Nepal, a topic with limited empirical exploration in the local context. Using monthly data from 2005 to 2024 and applying a Vector Autoregressive (VAR) framework, the study examines both long-run and short-run interactions. Stationarity tests revealed that all variables are integrated of order one, and lag selection criteria identified lag 1 as optimal for the VAR model. Johansen cointegration tests confirmed the absence of a long-run equilibrium relationship between EXR and stock market performance. However, Granger causality tests indicated a unidirectional short-run causal relationship from EXR to the NEPSE index. Variance decomposition analysis showed that while NEPSE is primarily driven by its own shocks, the influence of EXR is minimal but increases gradually over time. These findings imply that currency fluctuations have a short-term predictive role but limited long-term impact on Nepal’s stock market. The study contributes to the understanding of macroeconomic influences on stock market behavior and offers valuable insights for investors, policymakers, and financial analysts. The robust econometric approach, including VAR modeling, Granger causality, and diagnostic tests, ensures the reliability of the results. This research provides empirical evidence for informed decision-making in Nepal’s open and developing economy, emphasizing the importance of monitoring exchange rate movements in short-term investment strategies.